Aufgaben und Probleme der Stadtgeographie - Schöller, Peter (ERDKUNDE, 1953)
The purpose of this paper is to sketch concisely, on the basis of relevant publications over the last fifteen years, the resent development and present state of urban geography, the problems involved and methods employed. A survey is given of the natural and historical bases of urban development; the growth, expansion and delimitation of towns and cities, their internal structure and their classification; the functional relationships between town and country; the problem of urban individuality and type, and loss of national distinctiveness. As a result it becomes clear how even the most highly specialized investigations of particular problems or analyses of isolated data must take their place within the wider task of examining the town as a cultural-geographical entity, and researching into the structure, physiognomy, function and development of the urban region.